Propolis antiviral and immunomodulatory activity: A review and perspectives for COVID-19 treatment - Ripari, Nicolas [UNESP]; Sartori, Arthur Alves [UNESP]; Honorio, Mariana Da Silva [UNESP]; Conte, Fernanda Lopes [UNESP]; Tasca, Karen Ingrid [UNESP]; Santiago, Karina Basso [UNESP]; Sforcin, José Maurício [UNESP] (Oxford University Press (OUP), 2021)
Objectives Viral outbreaks are a frequent concern for humans. A great variety of drugs has been used to treat viral diseases, which are not always safe and effective and may induce adverse effects, indicating the need for new antiviral drugs extracted from natural sources. Propolis is a beemade product exhibiting many biological properties. An overview of viruses, antiviral immunity, propolis safety and its immunomodulatory and antiviral action is reported, as well as perspectives for coronavirus disease 2019 (COVID-19) treatment. PubMed platform was used for data collection, searching for the keywords propolis, virus, antiviral, antimicrobial and coronavirus. Key findings Propolis is safe and exerts antiviral and immunomodulatory activity; however, clinical trials should investigate its effects on individuals with viral diseases, in combination or not with antiviral drugs or vaccines. Summary Regarding COVID-19, the effects of propolis should be investigated directly on the virus in vitro or on infected individuals alone or in combination with antiviral drugs, due to its immunomodulatory and anti-inflammatory action. Propolis administration simultaneously with vaccines should be analyzed, due to its adjuvant properties, to enhance the individuals' immune response. The search for therapeutic targets may be useful to find out how propolis can help to control COVID-19.
Keywords: Antimicrobial action; Antiviral action; Coronavirus; Propolis; Virus